PENGEMBANGAN MODUL DESAIN GRAFIS BERBASIS PROJECT BASED LEARNING SISWA KELAS XI DESAIN KOMUNIKASI VISUAL DI SMKN 8 GARUT - Gita Permatasari; Deni Darmawan; Dian Rahadian (Universitas Negeri Makassar, 2026)
This research aims to develop a Project-Based Learning (PjBL)-based learning module for graphic design to improve the creative thinking skills of eleventh-grade students majoring in Visual Communication Design (DKV) at SMKN 8 Garut. The background of this research is based on the low level of creative thinking skills in students, the teacher-centered nature of learning, and the lack of project-based learning modules that meet the needs of the creative industry. The method used was Research and Development (R&D) with the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. Data collection techniques included observation, interviews, questionnaires, and documentation studies. Data analysis used qualitative descriptive analysis to assess the needs and development process, and quantitative analysis to measure the product's validity, practicality, and effectiveness through assessment results, questionnaires, and a comparison of pretest and posttest scores. The results showed that the developed PjBL-based learning module met the criteria for validity based on assessments by material and media experts, was practical for use in the learning process, and was effective in improving students' creative thinking skills. This improvement is evident in students' active engagement in learning, their ability to generate more varied and original ideas, and improved learning outcomes after using the module. Furthermore, the developed web-based module supports more contextual, independent learning, and aligns with industry needs. Thus, Project-Based Learning (PjBL) modules can be an innovative solution to improve the quality of graphic design instruction in vocational schools, particularly in developing students' creative thinking skills